Growth and Yield Response of Spring Maize to Zinc and Boron Combined with NPK in Banke District, Nepal - Acharya, Mahendra; Chhetri, Swastika; Acharya, Padma; Adhikari, Ravi Kiran (Agriculture Development Journal, 2025)
The experiment was carried out to evaluate the effect of zinc and boron along with nitrogen (N), phosphorus (P2O5 ) and potassium (K2O) on growth and yield of spring maize in Duduwa-6, Banke from March to July 2023.The study was conducted in Randomized complete block design including 4 replications and 5 treatments: a) Farmer’s practice 100:50 (N:P2O5 ) kgha-1, b) Recommended dose 160:60:40(N:P2O5 :K2O) kgha-1, c) Recommended N:P2O5 :K2O + 15kgha-1 zinc, d) Recommended N:P2O5 :K2O + 2kgha-1 boron and e) Recommended N:P2O5 :K2O + 15kgha-1 zinc + 2kgha-1 boron. Rampur hybrid-10 variety of maize was sown on sandy loam, neutral soil with medium in organic matter. The field data on phenology, crop growth, yield attributes, yield and economic of crop production were collected. The study revealed that grain yield of maize was significantly higher in fertilization rate of 160:60:40 (N:P2O5:K2O) kgha-1, together with the application of Zn 15kgha-1 and B 2kgha-1. The study has also revealed that use of micronutrients such as Zn and B is beneficial to enhance growth and yield of hybrid maize. The plant height was the highest with Recommended N:P2O5:K2O + Zn + B at earlier stage of crop growth but was statistically similar among different treatments at later stage of crop growth. The highest grain yield, harvest index and benefit cost ratio were recorded with the Recommended N:P2O5 :K2O + Zn + B while these parameters were the lowest with the farmer’s practice. Therefore, highest grain yield and maximum profit were obtained when fertilization rate of 160:60:40 (N:P2O5 :K2O) kg ha-1, together with the application of Zn 15kgha-1 and B 2kgha-1.